2007
DOI: 10.1111/j.1600-0846.2006.00200.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin conductance; validation of Skicon‐200EX® compared to the original model, Skicon‐100®

Abstract: The two Skicon instruments evaluated in this study correlated well, however, they displayed different levels depending on instrument main body and probes. Overall, the Skicon-200EX gave 1.6-fold higher value, and this instrument might be more sensitive than the original device, Skicon-100. In scientific reports, the type of instrument main body as well as probe shall be clearly specified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 9 publications
1
20
0
Order By: Relevance
“…This pilot study is the first to measure water content of the SC in different body sites with the Epsilon. Our findings showed significant differences among the body sites, in correspondence with previous studies that also showed this trend . Many factors could influence these regional differences, for example, variations in the presence of sebaceous glands and lipids, natural moisturizing factor (NMF), size of corneocytes, exogenous compounds on skin surface and occlusion .…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This pilot study is the first to measure water content of the SC in different body sites with the Epsilon. Our findings showed significant differences among the body sites, in correspondence with previous studies that also showed this trend . Many factors could influence these regional differences, for example, variations in the presence of sebaceous glands and lipids, natural moisturizing factor (NMF), size of corneocytes, exogenous compounds on skin surface and occlusion .…”
Section: Discussionsupporting
confidence: 89%
“…Our findings showed significant differences among the body sites, in correspondence with previous studies that also showed this trend. [5][6][7]12,13 Many factors could influence these regional differences, for example, variations in the presence of sebaceous glands and lipids, natural moisturizing factor (NMF), size of corneocytes, exogenous compounds on skin surface and occlusion. 4,12,14 Also, SC thickness variation could play a role; the smallest SC cell number is found in genital skin, followed by the face, neck, scalp, trunk, extremities and palmoplantar region.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Technical descriptions of the conductance measuring system have been published by Tagami (17–19). The Skicon 200 EX ® is a more recent version of the Skicon 200, which has been described by O'Goshi and Serup (20). The instrument measures the conductance (readings in μS units) of a single high‐frequency current at 3.5 MHz.…”
Section: Methodsmentioning
confidence: 99%